La gestión organización como herramienta impulsora de competitividad y sostenibilidad productiva en comunidades agrícolas ecuatorianas. - Zambrano Rosales, Efraín Eduardo (2021)
Organizational management is a managerial process that allows entities to be proactive, through the execution of established strategic objectives, to achieve competent results. In this sense, the agricultural producers of the Pilaló parish have developed their productive activities based on empirical management strategies, which generate uncertainties and improvisations in planting operations, as well as a significant drop in production and a marked deterioration in quality. of the product. The objective of the study is to propose an organizational management model that promotes competitiveness and productive sustainability of the agricultural communities of the investigated sector. The study design is non-experimental, with a quantitative approach. The results of the research highlight the need of the agricultural producers of the Pilaló parish to reorganize their competitive and productive processes, which generate unfavorable and complex situations that demand the need to have an Organizational Management Model for the stability and sustainability of the business. Once the organizational management design model is implemented, the agricultural communities in the area will have satisfactory growth and development in their processes. Business strengthening is guaranteed effectively and efficiently.